Kajian Tata Kelola PBJ (Pengadaan Barang & Jasa) Konstruksi Proyek Air Baku : Pendekatan Sistem Hukum Friedman (Studi Putusan PN Kupang No. 26/Pid.Sus-Tpk/2025/Pn.Kpg) - Kodrat Insany Taqwim (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study examines the governance of construction procurement for a raw water project through Lawrence M. Friedman’s legal system framework, using the District Court for Corruption Crimes in Kupang Decision No. 26/Pid.Sus-TPK/2025/PN.Kpg as the core legal material. Employing doctrinal legal research with statute, conceptual, and case approaches, the analysis treats the court decision not merely as an adjudicative outcome but as an institutional artifact reflecting systemic interactions among legal substance, legal structure, and legal culture. The findings demonstrate that procurement corruption emerges from a cumulative process in which regulatory discretion and fragmented norms enable procedural deviations to escalate into criminal liability. Structural weaknesses are reflected in disrupted accountability chains, limited early detection mechanisms, and ineffective supervisory coordination across procurement actors. Cultural dynamics further intensify risk through the normalization of informal practices, compliance understood as administrative formality, and integrity deficits in bureaucratic decision-making. The study contributes theoretically by refining Friedman’s framework for procurement governance analysis and methodologically by triangulating statutory norms, judicial reasoning, and governance literature to generate prescriptive reforms targeting normative coherence, institutional strengthening, and cultural transformation.